2020
DOI: 10.1186/s13104-020-4927-3
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing of virus-infected Cucurbita pepo samples revealed the presence of Zucchini shoestring virus in Zimbabwe

Abstract: Objectives: Plant-infecting viruses remain a serious challenge towards achieving food security worldwide. Cucurbit virus surveys were conducted in Zimbabwe during the 2014 and 2015 growing seasons. Leaf samples displaying virus-like symptoms were collected and stored until analysis. Three baby marrow samples were subjected to nextgeneration sequencing and the data generated were analysed using genomics technologies. Zucchini shoestring virus (ZSSV), a cucurbit-infecting potyvirus previously described in South … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This showed that DNA signatures belonged to 52 geminivuruses infecting crop hosts 35 geminiviruses infecting noncultivated plants, identified in different plant species. Their study demonstrated that HTS analyses can increase knowledge of virus diversity, and assist identification and detection of novel emerging known and unknown viruses without requirement for disease etiological information (Karavina et al, 2020).…”
Section: High-throughput Sequencing Tools In Viral Diagnosismentioning
confidence: 99%
“…This showed that DNA signatures belonged to 52 geminivuruses infecting crop hosts 35 geminiviruses infecting noncultivated plants, identified in different plant species. Their study demonstrated that HTS analyses can increase knowledge of virus diversity, and assist identification and detection of novel emerging known and unknown viruses without requirement for disease etiological information (Karavina et al, 2020).…”
Section: High-throughput Sequencing Tools In Viral Diagnosismentioning
confidence: 99%
“…Because of its broad detection spectrum and novel pathogen detection ability, it has recently become an increasingly popular tool for pathogen detection. It has been used in many crops, such as wheat [ 34 ], grapevine [ 35 ], citrus [ 36 ], fruit trees [ 37 ], cucurbit [ 38 ], sugarcane [ 10 ], grasses [ 7 , 38 ] etc. for viral pathogen detection.…”
Section: Introductionmentioning
confidence: 99%